Carotid Cavernous Fistula – Radiological Features - S. Sheetal; Nikhil Gladson; Chandana Ram; Joel Varghese Sujan (Archives of Medicine and Health Sciences)
Carotid cavernous fistula (CCF) is an abnormal vascular shunt from the carotid artery to the cavernous sinus. The characteristic clinical features include chemosis, proptosis, ocular bruit, headache, diplopia, and ophthalmoplegia. The classical radiological features on magnetic resonance imaging (MRI) include proptosis, extraocular muscle enlargement, dilatation of the superior ophthalmic vein, and ipsilateral cavernous sinus enlargement. We report the case of a 66-year-old female who presented with headache, redness of the right eye, and double vision, who had features of CCF on MRI.